The 2020 report of The Lancet Countdown on health and climate change: responding to converging crises. Issue 10269 (9th January 2021) - Watts, Nick; Amann, Markus; Arnell, Nigel; Ayeb-Karlsson, Sonja; Beagley, Jessica; Belesova, Kristine; Boykoff, Maxwell; Byass, Peter; Cai, Wenjia; Campbell-Lendrum, Diarmid; Capstick, Stuart; Chambers, Jonathan; et al.
Abstract : Translations: For the Chinese, French, German, and Spanish translations of the abstract see Supplementary Materials section.